FIGURATIVE LANGUAGE IN RIHANNA’S “SELECTED SONGS” - Marhamah Marhamah (Universitas Islam Sumatera Utara (UISU), 2018)
This research is concerned with the analysis of figurative language portrayed in Rihanna’s selected songs. Figurative language is a kind of literature that emphasize in connotation meaning than literary one. It is language that uses word or expression with a different meaning than literal interpretation. It can be found in literature and poetry where the writing appeals to the senses. It can do this by giving a word with a specific meaning, by comparing two things in such a way that it finds the comparison interesting or by using words that have unusual constructions or sounds.The objectives of the study are to identify the types of figurative language and to state how the figurative language is in Rihanna’s selected songs. Figurative language theory applied in this paper is proposed by Perrine (1969) stating that figurative languages are another way of adding extra dimension to language. The findings show that there are significant figurative language in Rihana’s selected songs: Hyperbole, Personification, Simile, Metaphor, Symbol, Repetition, Imagery, Alliteration, Metonymy, and Assonance.